2014
DOI: 10.1016/j.exer.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent degenerative transformations in the lipidome of chalazia

Abstract: The aim of this prospective study was to conduct histopathologic and lipidomic analyses of chalazia, in order to evaluate time-dependent changes in the lesion. Samples of surgically excised chalazia were collected over a period of 12 months from 10 patients (mean age 41 years; range, 23–58) with clinically diagnosed chalazia, who underwent scheduled surgery. The ages of chalazia varied from 2 to 28 weeks. To confirm the clinical diagnoses, the morphology of collected tissue samples was evaluated histologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Human meibum had been extensively characterized in our previous publications in detail [16, 2225, 3039, and references therein] and was used in this study only to compare it with meibum of mice. Notably, inter-donor variability in the molar ratios of major tested lipids (WE and CE) in meibum of normal, non-DE humans was found to be rather low [36, 38, 39] and not exceeding ±15%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human meibum had been extensively characterized in our previous publications in detail [16, 2225, 3039, and references therein] and was used in this study only to compare it with meibum of mice. Notably, inter-donor variability in the molar ratios of major tested lipids (WE and CE) in meibum of normal, non-DE humans was found to be rather low [36, 38, 39] and not exceeding ±15%.…”
Section: Methodsmentioning
confidence: 99%
“…TF/TFLL combination also serves as a lubricant [11] that smoothes movements of the eyeball and the eyelids, and improves visual acuity [12, 13]. In humans, diseases such as various forms of Dry Eye (DE) [14] and chalazion – an ocular lesion that typically originates from MG [15, 16] – have been linked to dysfunctionalities in MG, which result either in abnormal lipid secretions, or insufficient production or expression of meibum [17]. DE disease affects a large portion of the human population (between 8 and 30%, depending on the region and diagnostic criteria) [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that chalazia were mainly composed of macrophages, neutrophils and epithelial cells. 16,17 Moreover,…”
Section: Discussionmentioning
confidence: 99%
“…The lipid component of chalazion was different from normal meibomian gland lipids. 17 However, infrared meibomian gland photography is based on the theory that the lipid particles in the meibomian gland are excited by infrared rays and emit scattered light. 18 A chalazion is composed of granulomatous substances and abnormal lipids before treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation